A model biorefinery for avocado (Persea americana mill.) processing (2017)
This research investigated and evaluated a biorefinery for processing avocado Hass variety into microencapsulated phenolic compounds extract, ethanol, oil and xylitol. Avocado was first characterized for its potential valuable compounds; then, the techno-economic and environmental aspects of the biorefinery were developed and finally the total production costs and potential environmental impact of the proposed biorefinery were investigated. Four scenarios of the biorefinery were evaluated with different extent of mass and energy integration as well as the incorporation of a cogeneration system. Results indicated that the main fatty acid in the pulp of the investigated avocado variety was oleic acid (50.96%) and that this fruit contained significant amount of holocellulose (52.88% and 54.36% in the peel and seed, respectively). Techno-economic and environmental assessment suggested an attractive opportunity for a biorefinery for complete utilization of the avocado fruit as well the importance of the level of integration.